A PSYCHOLOGICAL STRUGGLE BETWEEN PRIDE AND CONSCIOUSNESS IN THE SHORT STORY "SOK" BY PUTU WIJAYA - I Ketut Sudewa (Prosiding Seminar Nasional dan Internasional HISKI, 2021)
Putu Wijaya is a writer who has a characteristic in his works. A prominent characteristic is that every literary character that appears always contains "terror" or "surprise" for the reader. One of his works related to "terror" for readers is a short story entitled "Sok". This short story is interesting to study because it contains a psychological "terror" between pride and consciousness. The problem discussed in this study is how the description of the psychological struggle between pride and awareness of the characters in the story "Sok" by Putu Wijaya and how the author expresses the psychological struggle. The method used in this research is a qualitative method through literature study with the theory of literary psychology and semiotics. Technical research as well as reading, listening, note-taking and interpretation techniques. The results showed that the character Aku in the short story "Sok" experienced a psychological struggle between the need for pride and awareness in his life. This endless struggle ends with my character realizing that actually my character has lost himself as a real human being. The psychological struggle of the character Aku is manifested in the form of "terror" for the reader in interpreting the importance of arrogance and awareness.